2017
DOI: 10.15288/jsad.2017.78.588
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Process Based Quality Indicators and Mortality for Patients With Substance Use Disorders

Abstract: Substance use disorders (SUDs) are associated with elevated rates of mortality. Little is known about whether receiving appropriate care is associated with lower mortality for patients with SUDs. This study examined the association between the receipt of care for SUDs and subsequent 12-and 24-month mortality. Method: This was a retrospective cohort study of veterans who received care for SUDs paid for by the Veterans Health Administration during October 2006-September 2007 (n = 339,966). Logistic regressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The few studies examining the link between utilization and mortality suggest that more service use could increase the receipt of preventive health services as well the early identification and management of new or worsening physical health problems (Druss et al, 2001; Meyer et al, 2014; Paddock et al, in press; Ronan and Herzig, 2016; Watkins et al, 2016). We found that frequent physician monitoring was associated with decreased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies examining the link between utilization and mortality suggest that more service use could increase the receipt of preventive health services as well the early identification and management of new or worsening physical health problems (Druss et al, 2001; Meyer et al, 2014; Paddock et al, in press; Ronan and Herzig, 2016; Watkins et al, 2016). We found that frequent physician monitoring was associated with decreased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation and engagement have been endorsed by the National Quality Forum as reliable and valid quality measures. Research has shown that initiation and engagement in substance use disorder treatment is associated with lower criminal justice involvement, unemployment, and mortality (3)(4)(5)(6)(7)(8).…”
Section: Highlightsmentioning
confidence: 99%
“…To achieve this objective, MODRN-OUD identified 20 access, quality and outcome measures and constructed these measures using the MODRN analytic approach outlined above. A number of sources were consulted to identify potential measures for inclusion: 1) a 2017 CMS guidance to State Medicaid Directors outlining indicators of access to high-quality OUD treatment [19], 2) a comprehensive review of over 20 medication-assisted treatment guidelines (and associated quality measures) performed for the US Department of Health and Human Services in 2015 [20], 3) American Society of Addiction Medicine (ASAM) guidlines [21], and 4) the peer-reviewed literature [222324252627]. MODRN-OUD findings point to significant variation in the prevalence of OUD, and in access and quality of treatment for OUD across state Medicaid programs.…”
Section: Modrn – Opioid Use Disordermentioning
confidence: 99%